Blood Gas Analysis (Astrup) in Children suffering from Gastroenteritis dehydration with Acidosis - Sutoto Sutoto; Sunoto Sunoto; Bambang M.; Sutejo Sutejo (Paediatrica Indonesiana, 1975)
Blood gas analysis and blood pH examinations have been carried out on 20 children suffering from severe gastroenteritis and dehydration. Ten patients were treated singly with half strength Darrow’s solution in 2.5% glucose containing potassium 17 mEq/L and lactate 26 mEq/ L as base corrector. The other 10 patients were given 3A solution (without potassium), containing lactate as base corrector as much as 53 mEq/L in the first 8 hours, followed by Darrow-Glucose (1:2) solution (with potassium).